1972
DOI: 10.1063/1.1678436
|View full text |Cite
|
Sign up to set email alerts
|

Energy Distribution Among Reaction Products. IV. X+HY (X ≡ Cl, Br; Y ≡ Br, I), Cl+DI

Abstract: The distribution of vibrational, rotational, and translational energies (symbolized by V′, R′, and T′) have been obtained for the products of the isotopic pair of reactions Cl + HI → HCl + I and Cl + DI → DCl + I. The experimental method was the ``arrested relaxation'' variant of the infrared chemiluminescence technique. Detailed rate constants k(V′, R′, T′) are reported in the form of contour plots for these reactions. The total detailed rate constants into specified vibrational quantum states for Cl+HI (summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…Previous studies on Heavy + Light-Heavy reaction systems show that the dynamics are dominated by kinematics rather than specific features of the potential energy surface itself. The extensive trajectory studies of Polanyi and co-workers (16)(17)(18)(19) shows that reactive collisions on such highly skewed surfaces are direct, with a strong propensity to cut the corner separating the entrance and exit valleys. These motions correspond to light atom transfer from configurations extended from equilibrium bond lengths with little momentum transfer to the departing heavy atoms, yielding reaction products that are highly vibrationally excited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on Heavy + Light-Heavy reaction systems show that the dynamics are dominated by kinematics rather than specific features of the potential energy surface itself. The extensive trajectory studies of Polanyi and co-workers (16)(17)(18)(19) shows that reactive collisions on such highly skewed surfaces are direct, with a strong propensity to cut the corner separating the entrance and exit valleys. These motions correspond to light atom transfer from configurations extended from equilibrium bond lengths with little momentum transfer to the departing heavy atoms, yielding reaction products that are highly vibrationally excited.…”
Section: Discussionmentioning
confidence: 99%
“…In proton transfer reactions in particular, the angle between the entrance and exit channels of the potential energy surface in scaled and skewed coordinates (15) is quite small, near 20" for particle transfer between bases of moderate mass. Trajectory studies by Polanyi and collaborators (16)(17)(18)(19) on such surfaces have shown that product energy release is determined more by the initial conditions of a trajectory than by details of the potential surface itself. At low collision energies, these studies show that reaction occurs through the mechanism of "mixed energy release", in which proton transfer occurs when both the breaking bond in the reagents and the bond forming in the products are extended.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50] In strongly exothermic proton transfer systems, the dynamics appear to be direct, partitioning the majority of the total energy into product vibration. As examples of the heavy + light-heavy mass combination in which the light particle is transferred in reaction, such systems exhibit the energy transfer motif of "mixed energy release", [35][36][37][38] in which the reaction occurs with the cleaving and incipient bonds in an extended configuration. This pattern for energy transfer is characteristic of "corner cutting" trajectories on scaled and skewed potential energy surfaces 51 in which the entrance and exit channels make a small angle with respect to one another and is therefore an intrinsic property of the potential energy surface.…”
Section: Discussionmentioning
confidence: 99%
“…Such light atom transfer is generally described by "mixed energy release", [35][36][37][38] in which both the cleaving and nascent bonds are extended from their equilibrium displacements. One can expect that the transfer will result in significant stretching excitation of the nascent N-D bond.…”
Section: A Deuterium Cation Transfermentioning
confidence: 99%
“…The idea of the simulation part was to form a basic setup for a future test stand for chemical cavities lasers within a numerical routine. The framework for the numerical routine [10,11] has been MATLAB7, a numerical computing environment by "The MATH-WORKS", ( Figure 5) since it offers a large range of inbuilt functions and visualization tools. In principle, the very simulations could have been done with any other sophisticated programming environment or language, but the MATLAB language offered the quite comfortable advantage of vector based variables useful for this prob-…”
Section: Ode's Solvers In Matlabmentioning
confidence: 99%